Deiksis Dalam Tajuk Rencana Harian Surat Kabar Tempo Dan Relevansi Dengan Pembelajaran Membaca Intensif Di SMP - Aryani, Novita Dwi, Dr. Yakub Nasuha,M.Hum (2017)
This study has two objectives. (1) Describing the form and meaning of deixis in the daily editorial of Tempo newspaper, (2) Describing the relevance of the result of deixis deformed analysis and meaning with intensive reading learning in junior high school. This research using description qualitative with the theory of triangulation theory is based on the assumption that fact can not be examined degree of trust with one or more theory in the problem studied. Technique of collecting data in this research is archive or document analysis. Data analysis technique used in this research is flow or braid analysis technique. The result of this research is the form and meaning of deixis in daily newspaper editorial of Tempo and relevance in junior high school. The deixis form contained in the daily editorial of the Tempo newspaper is the deixis outside-speech (eksofora) in the form of deixis persona, deixis place or space, and deixis time. Deiksis in-speech (endofora) in the form of deiksis anafora and deiksis katafora. This research can be used as teaching material in report writing material in junior high school. Especially on KD. 1.2 Findding information for discussion material through intensive reading. Teachers should integrate as well as be more selective in choosing teaching materials for students, before giving to teachers the teacher should read in advance whether the material is appropriate or not to be taught.